Exploring Instrumentation and Sensor Technologies for Highway Design and Construction Projects. Issue 9 (September 2020) - Harper, Christofer M.; Tran, Daniel; Jaselskis, Edward
With the infusion of emerging technologies into highway construction practices, state departments of transportation (DOTs) can make better informed decisions that positively influence cost, schedule, quality, and safety. DOTs are increasingly using instrumentation and sensor technologies for delivering highway projects across the U.S.A. Instrumentation devices and sensors include such technologies as remote sensing, real-time kinematics, global positioning systems, digital handheld devices, ground penetrating radar, and intelligent compaction/thermal profiling. These technologies are becoming commonplace in highway construction because of their capabilities to improve the construction process by making activities more efficient and more productive. However, the practices in using instrumentation and sensor technologies for highway construction vary among state DOTs. Therefore, this study investigates how DOTs employ the use of instrumentation and sensor technologies for highway construction. This study engaged a research methodology that included an extensive literature review, survey questionnaire, and case studies of state DOTs. Results show that 31 state DOTs use instrumentation and sensor technologies for monitoring work progress, conducting quality control and quality assurance, performing construction inspections, identifying optimal conditions and recording the placement of work, and locating utilities. The main barriers to using instrumentation and sensor technologies include analyzing the large amount of data, verifying the accuracy of the data, ensuring staff have the skills and knowledge to use the technologies efficiently, and assisting smaller contractors to gain the knowledge to use these technologies. The findings from this study provide recommendations and strategies for DOTs to implement instrumentation and sensor technologies effectively for highway construction.